2012
DOI: 10.1155/2012/682601
|View full text |Cite
|
Sign up to set email alerts
|

From Child-Robot Interaction to Child-Robot-Therapist Interaction: A Case Study in Autism

Abstract: Abstract. Troubles in social communication as well as deficits in the cognitive treatment of emotions are supposed to be a fundamental part of autism. We present a case study based on multimodal interaction between a mobile robot and a child with autism in spontaneous, free game play. This case study tells us that the robot mediates the interaction between the autistic child and therapist once the robot-child interaction has been established. In addition, the child uses the robot as a mediator to express posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Giannopulu and Pradel [26] have documented a case of a child with autism using a robot as a mediator for his interaction with a therapist in a free play scenario. The robot had a very simple design: a schematic facelike cover made of geometric shapes (circles for eyes and mouth, and triangle for nose) on top of a remotecontrolled locomotion hardware, able to move forward, move back and swivel.…”
Section: Increasing Social Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Giannopulu and Pradel [26] have documented a case of a child with autism using a robot as a mediator for his interaction with a therapist in a free play scenario. The robot had a very simple design: a schematic facelike cover made of geometric shapes (circles for eyes and mouth, and triangle for nose) on top of a remotecontrolled locomotion hardware, able to move forward, move back and swivel.…”
Section: Increasing Social Motivationmentioning
confidence: 99%
“…HRI studies of robots intervening in human-human interactions vary widely in their scope, and are scattered across domains of application, using very different robot designs in a variety of context. Some are simply case studies (e.g., [26]), others engage larger participant samples (e.g., [27]), some studies investigate the effects of the robot in the context of specific tasks (e.g., [20]), some leave the interaction free and open to what participants want to make of it, constrained just by the robots capabilities (e.g., [28]). Some of the robots used are designed with clinical applications in mind, such as assisting children with autism (e.g., [29]) or providing couples therapy (e.g., [30]), but many of them are intended for general use, for purposes such as promoting inter-generational interactions (e.g., [31]).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [32] have developed a physiology-based affect-inference mechanism for robot-assisted intervention where the robot can detect the affective states of a child with ASD. In other evaluations by [24], [33] and [34], videos were recorded during the child-robot interactions, and the recordings were analysed at a later date for qualitative data. In most of the studies of robots in autism therapy, the amount of qualitative data outweighs the quantitative data; therefore researchers need to focus more on methods for collecting quantitative data in order to obtain substantial support for validity of research.…”
Section: Evaluating the Effectiveness Of Assistive Robots In Autimentioning
confidence: 99%
“…As in real human interaction, the child and the robot altered their responses. All movements were constant and standardized (see also [17], [18]). …”
Section: Protocolmentioning
confidence: 99%
“…Using a multimodal cogmtlve nonverbal approach (visual, tactile, manipulation, posture) [17] which was also related to an emotional one [18], we have shown that a mobile toy robot "GIPY I" could be used as a neural mediator to bring neurocognitive improvements to autistic children. The multimodal cognitive interactions could be thought of as the building block from which expressive language could emerge.…”
Section: Introductionmentioning
confidence: 99%